Goods Booking System In WIJAYA Printing Company - Diana Marta; Yulina Yulina, SKom., MMSI. (Jurnal Sistem Informasi, 2004)
In an age of globalization era is the all sophisticated and modern developments in science and technology are advancing rapidly. One of progress is the use of computers that have been widely used the entrepreneur as a tool for their business activities. Starting from mid-level businessmen to top-level businessmen. By using the computer all transactions will sale items stored neatly and orderly. System sales are currently running on the company often have difficulty in doing data collection of goods sold, and the calculated result of booking and reservation sales to make his report.For that need to be made at the company's computerized system, where the data will be easily processed into accurately and quickly. Checking goods obtained accurate results and the calculation of bookings will be stored properly.